2013
DOI: 10.7567/apex.6.112302
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Bulk Minority-Carrier Lifetime in BaSi2Earth-Abundant Absorber Films by Utilizing a Drastic Enhancement of Carrier Lifetime by Post-Growth Annealing

Abstract: We have successfully determined the bulk minority-carrier lifetime in BaSi2 epitaxial films by utilizing a drastic enhancement of lifetime by post-growth annealing at 800 °C, which is attributed to strain relaxation. From the film-thickness dependence of lifetime, we reveal that the bulk lifetime is 14 µs, which is long enough for thin-film solar cell applications. In addition, the sum of surface and interface recombination velocities is found to be as low as 8.3 cm/s presumably due to the ionic nature of BaSi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
91
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(95 citation statements)
references
References 23 publications
3
91
1
Order By: Relevance
“…10 lm) 17 and long minority-carrier lifetime (ca. 10 ls), 18,19 even in multidomain a-axis-oriented BaSi 2 epitaxial layers, have confirmed that BaSi 2 could be a candidate for thin-film solar cells. The six-fold symmetry of Si(111) means that a-axis-oriented BaSi 2 can be grown epitaxially on Si(111) with its three epitaxial variants rotating around the surface normal at 120 with respect to each other.…”
mentioning
confidence: 74%
“…10 lm) 17 and long minority-carrier lifetime (ca. 10 ls), 18,19 even in multidomain a-axis-oriented BaSi 2 epitaxial layers, have confirmed that BaSi 2 could be a candidate for thin-film solar cells. The six-fold symmetry of Si(111) means that a-axis-oriented BaSi 2 can be grown epitaxially on Si(111) with its three epitaxial variants rotating around the surface normal at 120 with respect to each other.…”
mentioning
confidence: 74%
“…Semiconducting barium disilicide (BaSi 2 ), 1,2 composed of earth-abundant elements, has all these properties such as a band gap of 1.3 eV, 3 a large α of 3 × 10 4 cm -1 at 1.5 eV, [3][4][5][6] inactive grain boundaries, 7 and a large minority-carrier lifetime (τ ∼ 10 µs). 8,9 Since BaSi 2 can be grown epitaxially on a Si substrate 10 and its band gap can be increased by adding other elements such as Sr and C, 11,12 BaSi 2 is a material of choice for targeting η > 30% in Si-based tandem structure solar cells. We have achieved η approaching 10% in a p-BaSi 2 /n-Si heterojunction solar cell capped with a pure amorphous Si (a-Si) layer by an electron-beam (EB) evaporation.…”
mentioning
confidence: 99%
“…[1][2][3][4] Large absorption coefficients come from the band structure of BaSi 2 , where the localized Ba d-like states form flat energy bands in the conduction band. [5][6][7] Minority-carrier properties, such as a long minority-carrier diffusion length (ca.10 lm) 8,9 and a long minority-carrier lifetime (ca.10 ls), [10][11][12] in a-axis-oriented undoped n-type BaSi 2 epitaxial films spurred interest in this material. One of the striking features of this material is the fact that both large minority-carrier diffusion length and large absorption coefficient are available.…”
mentioning
confidence: 99%